2013
DOI: 10.1177/1753193413493386
|View full text |Cite
|
Sign up to set email alerts
|

Modified osteotomy (Kanaya’s procedure) for congenital proximal radioulnar synostosis with posterior dislocation of radial head

Abstract: Outcomes of Kanaya's procedure for congenital proximal radioulnar synostosis varied depending on the type of radial head dislocation. In our series of 14 patients with 17 forearms who underwent Kanaya's original procedure, the postoperative total rotation arc of the forearm was unsatisfactory in cases with posterior radial head dislocation. We examined the outcomes with respect to the type of radial head dislocation and radial shaft curvature. Radial shafts with a posterior radial head dislocation had only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 13 publications
0
24
0
3
Order By: Relevance
“…Surgical intervention is recommended by most surgeons when the loss of forearm rotation causes the patient to complain of functional difficulties. To date, two types of surgical treatments have been described: mobilization of the synostosis (Funakoshi et al, 2004;Jones et al, 2004;Kanaya and Ibaraki, 1998;Kao et al, 2005;Sakamoto et al, 2014), which frequently results in recurrence of the ankylosis with unsatisfactory results (Kanaya and Ibaraki, 1998;Miura et al, 1984;Sachar et al, 1994); and rotational osteotomy, which provides functional improvement (El-Adl, 2007;Griffet et al, 1986;Horii et al, 2014;Hung, 2008;Lin et al, 1995;Ogino and Hikino, 1987;Ramachandran et al, 2005;Shingade et al, 2014;Simmons et al, 1983). Therefore, rotational osteotomy is the accepted treatment for congenital radioulnar synostosis.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention is recommended by most surgeons when the loss of forearm rotation causes the patient to complain of functional difficulties. To date, two types of surgical treatments have been described: mobilization of the synostosis (Funakoshi et al, 2004;Jones et al, 2004;Kanaya and Ibaraki, 1998;Kao et al, 2005;Sakamoto et al, 2014), which frequently results in recurrence of the ankylosis with unsatisfactory results (Kanaya and Ibaraki, 1998;Miura et al, 1984;Sachar et al, 1994); and rotational osteotomy, which provides functional improvement (El-Adl, 2007;Griffet et al, 1986;Horii et al, 2014;Hung, 2008;Lin et al, 1995;Ogino and Hikino, 1987;Ramachandran et al, 2005;Shingade et al, 2014;Simmons et al, 1983). Therefore, rotational osteotomy is the accepted treatment for congenital radioulnar synostosis.…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative range of pronation and supination in motion-preserving techniques has eventually been assessed in three studies [ 9 , 23 , 24 ]. The mean fixed deformity noted in supination and pronation was 16.1° (25° to neutral) and 40° (neutral to 80°), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Oka et al (2006) reported that postoperative range of motion (ROM) was limited and the axis of rotation was displaced from its normal location in cases with dislocation of the radial head on 3D motion analysis. Sakamoto et al (2014) found that the radial shaft in forearms with posterior dislocation had one abnormal curvature and that corrective osteotomy of the central part of the radius improved ROM.…”
Section: Discussionmentioning
confidence: 97%
“…The radius and ulna showed a large tendency to have internal rotation deformities, not seen on plain radiographs. Several authors have reported that the outcome of separation and mobilization surgery is unsatisfactory in patients with severe pronation ankylosis and posterior dislocation of the radial head (Kanaya and Ibaraki, 1998; Kinjo et al., 2008; Oka et al., 2006; Sakamoto et al., 2014). They reported that the forearm rotation was limited and the centre of the rotation arc was biased toward pronation in these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation